MENGEMBANGKAN FRAMEWORK IMPLEMENTASI SISTEM OTOMASI PERPUSTAKAAN BERBASIS INTERNET OF THINGS : DEVELOPING FRAMEWORK IMPLEMENTATION OF IOT-BASED LIBRARY AUTOMATION SYSTEM - Totok Mulyono (Jurnal Teknologi dan Terapan Bisnis, 2019)
Today Information and Communication Technology (ICT), such as the Internet of Things (IoT), has a decisive influence on all aspects of human life. IoT as a dominant phenomenon is a transformation of daily life through the use of intelligent functions such as Radio Frequency Identification (RFID) and Wireless Sensor Technology Networks (WSN). Along with the development of IoT in size and dimensions thus increasing many community contexts; like, a traditional library system. This study proposes an execution framework on the use of IoT to update conventional library structures and schemes to smart online systems. IoT enables real-time connectivity of physical objects (such as books or other types of text) through the use of RFID tags and sensors. Monitoring books in real time and geographic location of objects are some of the characteristics of using IoT tags. These IoT features enable the implementation of library staff through supply chains, integration with various types of technologies such as databases, data collection, and cloud systems. The Internet of Things also offers an overview of links between a large number of universities and libraries in the world in real time and at any time. It was concluded that the application of IoT in library management systems became a promising structure that could play an important role in organizing human knowledge and in accessing information to help researchers, designers and officers in more efficient and intelligent ways.